First records of Ungla Navás (Neuroptera: Chrysopidae) from Venezuela, with descriptions of seven new species - Sosa, Francisco (Zootaxa, 2015)
Ungla Navás is a small and relatively unstudied genus of Neotropical Chrysopini (Neuroptera: Chrysopidae: Chrysopinae) from Central and South America. Here, the genus is reported from Venezuela for the first time, and seven new species are described: Ungla demarmelsi sp. nov.; Ungla diazi sp. nov.; Ungla curimaguensis sp. nov.; Ungla martinsi sp. nov.; Ungla nigromaculifrons sp. nov.; Ungla rubricosa sp. nov.; and Ungla yutajensis sp. nov.